Sex and Sanctity in the Apocryphal Acts of Andrew: A Christian Bedtrick and Its Biblical Bedrock - Hadjittofi, Fotini; Sivan, Hagith (2024)
In the apocryphal Acts of Andrew, a familiar double plot of sex and mistaken identity features Maximilla, a recently converted wife, tricking her pagan husband, Aegeates, into bedding her masked maid in order to retain the purity of her own bed. In resorting to this stratagem of sexual deception, the heroine of this tale behaves in a manner that contemporary Christians would (and did) find scandalous and unacceptable. This article investigates how this unique, sanctified bedtrick mobilizes different traditions (both Greco-Roman and biblical), subverts the predominant model of the Christian wife, and constructs a peculiar, alternative ideal. The Christian bedtrick evokes mythical and novelistic patterns but presents its instigator as paradoxically chaste—the opposite of her depraved analogues in myth and novel. The text also evokes biblical bedtricks, but only to challenge the emphasis on survival through procreation at all cost that underpins most of the bedtricks in Genesis. The article argues, finally, that the bridal switch between Rachel and Leah in Genesis 29 provides the closest biblical parallel for Maximilla's strategy. The striking apocryphal bedtrick also bears intriguing similarities to two texts that clearly hark back to the bridal switch of Genesis 29: an ancient Jewish "novel" (Josephus, Jewish Antiquities 12.154–236) and an exegetical vignette from rabbinic midrash (Lamentations Rabbah proem 24) that employ "holy" bedtricks in the interests of individual or collective salvation.